2011
DOI: 10.1039/c1pp05106g
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the fluorescence light-up effect of amino-substituted benzo[b]quinolizinium derivatives in the presence of biomacromolecules

Abstract: A comparative study of the ability of amino-substituted benzo[b]quinolizinium derivatives to act as DNA- or protein-sensitive fluorescent probes is presented. Spectrophotometric titrations, DNA denaturation studies and viscometric titrations showed that all tested aminobenzo[b]quinolizinium derivatives intercalate into DNA with binding constants K(b) = 10(4)-10(5) M(-1). The intense fluorescence of the 9-aminobenzo[b]quinolizinium (Φ(fl) = 0.41) as well as the intrinsically very weak emission of the 7-aminoben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…It was reported that quinolizinium derivatives can bind with biomacromolecules such DNA and proteins, exhibiting a fluorescence turn-on effect, because of a restricted conformation flexibility. 59,60 Similar effects were observed with quinoliziniums 1 and 2.…”
Section: Fluorescencesupporting
confidence: 82%
“…It was reported that quinolizinium derivatives can bind with biomacromolecules such DNA and proteins, exhibiting a fluorescence turn-on effect, because of a restricted conformation flexibility. 59,60 Similar effects were observed with quinoliziniums 1 and 2.…”
Section: Fluorescencesupporting
confidence: 82%
“…The emission shift is likely the result of suppressed deactivation pathways in the excited state, namely torsional relaxation, because of the reduced conformational flexibility within the binding site. 38 In particular, this effect was observed for quinolizinium derivatives, 39 namely the 9-(4-dimethylaminophenyl)benzo[ b ]quinolizinium in the presence of ct DNA or 22AG , 11 and berberine and sanguarine in the presence of abasic site-containing DNA. 40 This explanation is consistent with the observation that the red-shifted emission band of 4b is also present in a highly viscous solvent such as glycerol, in which the conformational flexibility is reduced leading to two distinct emitting species (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature there are many fluorescent compounds e.g. Ethidium bromide, acridine orange and methylene blue and they are normally used to probe the DNA structure in drug-DNA interactions [1][2][3][4][5][6][7][8][9][10][11][12]. The visualization of DNA labelled with a fluorescent dye through optical microscopy was reported [13,14].…”
Section: Introductionmentioning
confidence: 99%